Erratum: Callaway et al. Alternatives to Antibiotics: A Symposium on the Challenges and Solutions for Animal Health and Production. Antibiotics 2021, 10, 471 - Todd R. Callaway; Hyun Lillehoj; Rungtip Chuanchuen; Cyril G. Gay (MDPI AG, 2021)
The authors would like to make the following corrections to the published paper [...]